Personal Data Hacking: A Critical Analysis of Islamic Criminal Law and Islamic Jurisprudence - Munifah, Munifah; Mulyo, Mufrod Teguh (Universitas Islam Sultan Agung, 2025)
This research will examine the rise of social media hacking behaviour from the perspective of Islamic Criminal Law and Islamic Law. The issues discussed in this study include how Islam addresses the laws related to individuals who commit crimes against the right to privacy and personal data, as well as the urgency of personal data protection in social media within the context of Islamic law and the Muslim response to the digital era. This research employs a descriptive-qualitative methodology with in-depth data analysis, incorporating juridical and Islamic criminal law approaches. Primary data is derived from cases and behavioural data pertaining to personal data. Secondary data encompasses primary, secondary, and tertiary legal materials. Primary legal materials include binding legal sources such as legislation, legislative records, and court decisions. The findings of this study indicate that Islam underscores the importance of maintaining the dignity and privacy of individuals through the principles of honour protection (Ḥifẓ al-’Irḍi). Every Muslim is obligated to uphold the security of personal data and to advocate for the implementation of laws that protect individual rights from cyber threats. In order to enhance the security of personal data, it is recommended that Islamic principles be integrated into current laws, ensuring they are based on both positive law and maqashid sharia. Furthermore, improving digital literacy in accordance with Islamic teachings serves as a strategic initiative to raise public awareness of the significance of protecting privacy in the digital age. This study concludes that violations of personal data in the digital realm, such as identity theft and unauthorised information dissemination, can be classified under punishment (taʿzīr) within Islamic criminal law due to the absence of explicit provisions in ḥudūd and qiṣāṣ. It highlights the urgency of protecting personal data in social media and advocates for the application of Islamic legal principles, such as ḥifẓ al-‘irḍ as a foundation for safeguarding individual privacy in the digital era.